Chronic AT1 blockade improves glucose homeostasis in obese OLETF rats. Issue 3 (June 2018) - Rodriguez, Ruben; Minas, Jacqueline N; Vazquez-Medina, Jose Pablo; Nakano, Daisuke; Parkes, David G; Nishiyama, Akira; Ortiz, Rudy M
Abstract : Obesity is associated with the inappropriate activation of the renin-angiotensin system (RAS), which increases arterial pressure, impairs insulin secretion and decreases peripheral tissue insulin sensitivity. RAS blockade reverses these detriments; however, it is not clear whether the disease state of the organism and treatment duration determine the beneficial effects of RAS inhibition on insulin secretion and insulin sensitivity. Therefore, the objective of this study was to compare the benefits of acute vs chronic angiotensin receptor type 1 (AT1 ) blockade started after the onset of obesity, hyperglycemia and hypertension on pancreatic function and peripheral insulin resistance. We assessed adipocyte morphology, glucose intolerance, pancreatic redox balance and insulin secretion after 2 and 11 weeks of AT1 blockade in the following groups of rats: (1) untreated Long-Evans Tokushima Otsuka (lean control; n = 10), (2) untreated Otsuka Long-Evans Tokushima Fatty (OLETF; n = 12) and (3) OLETF + ARB (ARB; 10 mg olmesartan/kg/day by oral gavage; n = 12). Regardless of treatment duration, AT1 blockade decreased systolic blood pressure and fasting plasma triglycerides, whereas chronic AT1 blockade decreased fasting plasma glucose, glucose intolerance and the relative abundance of large adipocytes by 22, 36 and 70%, respectively. AT1 blockade, however, did not improve pancreatic oxidative stress or reverse impaired insulin secretion. Collectively, these data show that AT1 blockade after the onset of obesity, hyperglycemia and hypertension improves peripheral tissue insulin sensitivity, but cannot completely reverse the metabolic derangement characterized by impaired insulin secretion once it has been compromised.